UPAYA MENINGKATKAN KECERDASAN EMOSIONAL MAHASISWA JURUSAN BIMBINGAN KONSELING FIP UNNES SEMESTER I TAHUN AKADEMIK 2009/2010 MELALUI LAYANAN KONSELING KELOMPOK - Saraswati, Sinta; Kustiono, -; Wahyu Eny, Biif Nur (Jurnal Penelitian Pendidikan, 2010)
The problem in this research is: "How is the implementation of group counseling services that can enhance emotional intelligence of students of Guidance Counseling Department of FIP of Unnes?" The purpose of this research was to find out how the implementation of group counseling services (KKp) can improve studentÃ¢â‚¬Å¸s intelligence emotional. This is a classroom action research with first semester students of BK department as subjects. The object of observation in this study is to increase The students' emotional improvement is observed using problem checklist. The research was performed in 3 cycles. The results shows the emotional intelligence of students decreases by average of 4.32% for the first cycle, increases by average of 16.31% for second cycle, and increases by average of 10.60% for the third cycle. The total improvement is 22.52%. Thus, Group Counseling Service (KKp) is effective to improve students' emotional intelligence. Keywords: emotional intelligence, guidance counseling, group counseling services